Efektivitas Model Pembelajaran PjBL Berbantu Media Scrapbook terhadap Keterampilan Kolaborasi dan Hasil Belajar Kognitif Siswa - Silvi Nur Isnaini; Pradika Adi Wijayanto (Universitas Indraprasta PGRI, 2026)
This study aims to determine the effectiveness of the Project Based Learning (PjBL) model assisted by scrapbook media in improving collaboration skills and cognitive learning outcomes of seventh-grade students in Social Studies at SMP Negeri 1 Boja. The research employed a quantitative approach using a Quasi-Experimental method with a Nonequivalent Control Group Design. The sample consisted of class VII C as the experimental group and class VII E as the control group, selected through purposive sampling. Data were collected through tests (pretest and posttest) to measure cognitive learning outcomes and observation sheets to assess collaboration skills. Data analysis employed descriptive percentage analysis for students’ collaboration skills and an independent sample t-test for cognitive learning outcomes. The results showed that the average posttest score of the experimental class was 81.33, higher than the control class at 66.66, with a significance value of 0.000 (< 0.05), indicating a significant difference between the two classes. The collaboration skills of the experimental class also fell into the good to very good categories, with 52% of students categorized as very good and 48% as good, particularly on indicators of active participation, teamwork, and fair task distribution. Thus, the PjBL model assisted by scrapbook media is proven effective in enhancing students’ collaboration skills and cognitive learning outcomes..